Desarticular el indigenismo oficial. Miradas al Instituto Nacional Indigenista (1940-1960) - Paula López Caballero (Université Paris 3, 2021)
Despite its centrality for the discipline of anthropology and for the practice of indigenista policy, the ‘field’ has rarely been interrogated as a productive site of historical analysis. In this article I explore a set of ethnographic fieldnotes produced for the Instituto Nacional Indigenista between 1948 and 1960 in different parts of Mexico. I show that these documents allow us to reconstruct another history of indigenismo and anthropology. One that does not start out from their doctrines, programs and outcomes, but rather focuses on the mechanisms, actors and contradictions that condition the construction and reproduction of this institutional project, but down at the bottom, in the field. This ‘capilary’ gaze on the institution allows me to problematize what I call the ‘indigenista archive’, that is, the system of discursivities that this institution was in the process of consolidating. Thus by using the field to disarticulate these institutional narratives, I intend to offer, in the last analysis, an ethnography of the State.